Iron-copper mineralization associated with metagabbro in Mirawa Village, Kurdistan region, northeastern Iraq - Yara, Irfan Omar Mousa; Mohammad, Yousif Osman (Sulaimani Journal for Pure and Applied Sciences, 2018)
Mirawa iron-copper mineralization in Mirawa village, Kurdistan region, occurs as a zone of 15 m thick within the metagabbro of the Mawat Ophiolite. It is hosted by brecciated amphibolite facies gabbroic rocks with a northwest–southeast trending shear zone. Amphibole, magnetite, plagioclase, quartz, epidote, chlorite, clinopyroxene and chalcopyrite represent the mineral constitutes of metagabbro. Metamorphic conditions have been estimated from the green metamorphic amphibole replacing primary magmatic clinopyroxene (M1, 500 < T < 560 °C; 4.3 < P < 5.2 kbar) and retrograde actinolite (white amphibole) replacing the green amphibole due to continuous decreasing pressure and temperature (M2, 415 < T < 480 °C; 1.9 < P < 2.3 kbar). Occurrence of quartz with ironcopper mineralization hydrothermal fluids played a significant role during metamorphism. Chlorite and epidote were formed at the late stage of metamorphism. Iron-copper mineralization occurred in two paragenetic stages. Coarse grains of magnetite, chalcopyrite and pyrite formed during the first stage of mineralization representing syngenetic mineralization. Magnetite is the main Fe-ore mineral and it is characterized by large euhedral to subhedral grains with ilmenite exsolution lamellae. The second stage is epigenetic where mineralization is characterized by the formation of secondary minerals, replacing the primary minerals. Hematite replaces primary magnetite along the rim. Chalcopyrite, pyrite and magnetite were replaced by goethite whereas covellite overgrows chalcopyrite forming a corona texture. Fine-grained idomorphic aggregates of magnetite are dominant in the second stage and seem to be formed from iron liberated from pyroxene and other iron-bearing minerals. Microstructural orientation of the coarse-grained magnetite indicates a NW-SE direction for the maximum stretching of strain ellipse.
Keywords: Ironcopper; Mineralization; Metagabbro; Geothermometry